Grade VIII Junior-Secondary Learners’ Views of Duolingo for English Vocabulary Learning: A Case Study at a Bogor Private Junior High School - Nabilah Najah Kaniah; Iwan Ridwan; Dedeh Kartini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Three themes emerged from a qualitative single-case study of Grade VIII students at a private junior high school in Bogor, Indonesia: gamified micro-goals sustained short, low-anxiety practice; immediate, multimodal feedback (checks, audio, tiles, spaced recycling) supported noticing, pronunciation, and retention; and autonomy and everyday fit were valued, yet transfer to extended speaking/writing was limited without teacher-led bridging tasks. To contextualize these results, Self-Determination Theory and Mobile-Assisted Language Learning framed the inquiry. A syllabus-aligned vocabulary screening informed the purposive selection of six learners spanning low/medium/high readiness. Each focal learner completed one supervised Duolingo session, observed with a structured checklist, then participated in a semi-structured interview; data were analyzed using reflexive thematic analysis. The findings suggest that out-of-class app exposure is most beneficial when coupled with brief, in-class production activities and criteria-based feedback to move learners from recognition to controlled use of target lexis. The study is limited by its single-class scope and one-session design; future research should examine multi-week classroom integration and task-based measures of productive skills.